Child and parent experiences of childhood epilepsy surgery and adjustment to life following surgery: A qualitative study. (December 2020) - O'Brien, Jennifer; Gray, Victoria; Woolfall, Kerry
Highlights: Concerns about long term wellbeing, risks to safety, social isolation and hope for a 'normal' life contributed to the decision to pursue epilepsy surgery. Children and parents described post-surgery improvements in seizure control, alongside improved psychological wellbeing, quality of life, social relationships and family functioning. Families also experienced difficulties adjusting post-surgery as children missed aspects of their pre-surgical life and struggled with a loss of their identity. Families would benefit from additional information and clinical support to help them prepare for, and adjust to, a new normality of life without seizures. Abstract: Purpose: Surgical procedures are increasingly used as a treatment option for paediatric patients with refractory epilepsy as seizure relief is often assumed to be associated with positive psychosocial and quality of life outcomes. This study aimed to explore children's and parents' experiences of epilepsy surgery and associated psychosocial outcomes. Methods: Semi-structured interviews were conducted with parents and their children aged between 7 and 17 years old, who had undergone epilepsy surgery within the previous six months to three years. Analysis of interview data was interpretive and iterative, using the constant comparison approach, to develop a rich understanding of family experiences throughout the surgery journey. Results: Interviews were conducted with 16 participants including seven children (aged 8–15 years) and their nine parents. Epilepsy had significant impact on quality of life for children and parents. Concerns about long term wellbeing, risks to safety and hope for a 'normal' life contributed to the decision to pursue surgery. All participants described improvements in seizure control, alongside improved psychological wellbeing, quality of life, social relationships and family functioning. However, children and their parents experienced difficulties adjusting to a new post-surgical identity and 'missing' aspects of their pre-surgical life with epilepsy. Conclusions: Epilepsy surgery had a positive impact on participants' lives, but families described difficulties in adjusting to postsurgical changes and leading a 'normal' life. Our findings suggest that families would benefit from additional information and clinical support leading up to epilepsy surgery to help them prepare for and adjust to a life without epilepsy.